Berardinelli-Seip Congenital Lipodystrophy Discovered Following a STEMI Event - Francisca Beires; Helena Greenfield; José Brito da Silva; João Gil; Nuno Moreno (European Journal of Case Reports in Internal Medicine, 2022)
A 60-year-old man, with a history of familial lipodystrophy, hypertriglyceridaemia, hepatic steatosis and bone cysts, was admitted due an acute coronary event. Coronary angiography showed significant stenosis in the left anterior descending artery, which was treated. Transthoracic echocardiography showed a slightly dilated left ventricle with diffuse and heterogeneous thickening of its walls, slightly decreased left ventricular function and reduced global longitudinal strain. Due to these echocardiographic findings, cardiac magnetic resonance imaging was requested, which identified intramyocardial diffuse fibrosis of the basal septum and points of insertion of the left and right ventricles, without oedema, microvascular obstruction or myocardial infarction. Owing to the constellation of symptoms and distinctive features on cardiac imaging, a diagnosis of Berardinelli-Seip congenital lipodystrophy (BSCL) was suspected, which was confirmed through genetic testing of the pathogenic variants in BSCL2 and AGPAT2. BSCL is a rare autosomal recessive syndrome characterized by the congenital absence of adipose tissue and triglyceride deposition in other tissues, such as muscle, liver and heart.